3D digital headform models of Australian cyclists. (March 2017) - Ellena, Thierry; Skals, Sebastian; Subic, Aleksandar; Mustafa, Helmy; Pang, Toh Yen
Abstract: Traditional 1D anthropometric data have been the primary source of information used by ergonomists for the dimensioning of head and facial gear. Although these data are simple to use and understand, they only provide univariate measures of key dimensions. 3D anthropometric data, however, describe the complete shape characteristics of the head surface, but are complicated to interpret due to the abundance of information they contain. Consequently, current headform standards based on 1D measurements may not adequately represent the actual head shape variations of the intended user groups. The purpose of this study was to introduce a set of new digital headform models representative of the adult cyclists' community in Australia. Four models were generated based on an Australian 3D anthropometric database of head shapes and a modified hierarchical clustering algorithm. Considerable shape differences were identified between our models and the current headforms from the Australian standard. We conclude that the design of head and facial gear based on current standards might not be favorable for optimal fitting results. Highlights: Four new headforms are created based on the 3D scanned data of Australian cyclists. The new models are compared to the standard Australian headforms. Large shape differences are identified with the current standard. A new clustering method of head shape is used to compute the groups. Should encourage designers to use 3D data more extensively in the design process.